3D-networked carbon nanotube/diamond core-shell nanowires for enhanced electrochemical performance - Lee, Seung-Koo; Song, Min-Jung; Kim, Jong-Hoon; Kan, Tae-Seok; Lim, Young-Kyun; Ahn, Jae-Pyoung; Lim, Dae-Soon (NATURE PUBLISHING GROUP, 2014)
A boron-doped diamond/carbon nanotube (BDD-CNT) hybrid material with a core-shell three-dimensional random network structure was fabricated using the electrostatic self-assembly of nanodiamond. In general, CNTs are easily etched out as hydrocarbons or transformed to graphitic clusters at defect sites in hydrogen-rich environments (that is, the typical conditions employed for diamond deposition). However, attaching a dense layer of nanodiamond particles to the outer wall of the CNTs suppressed CNT etching and promoted BDD growth. To attach the dispersed nanodiamond particles on the CNT surface, we used an electrostatic self-assembly technique in which the surface charges on the CNTs and the nanodiamond were controlled using cationic and anionic polymers. Following BDD deposition, the electrochemical properties of the BDD-CNT structures were examined by cyclic voltammetry and electrochemical impedance spectroscopy. The results indicated that the BDD-CNTs exhibited enhanced electron transport efficiency, large effective surface areas and high sensitivity, with a remarkably low detection limit.
Keywords: BORON-DOPED-DIAMOND; THIN-FILMS; HYDROGEN-PEROXIDE; ELECTRON-TRANSFER; SENSOR